Data from: Mitochondrial membranes in cardiac muscle from Antarctic notothenioid fishes vary in phospholipid composition and membrane fluidity ... - Biederman, Amanda M.; Kuhn, Donald E.; O'Brien, Kristin M.; Crockett, Elizabeth L. (Dryad, 2019)
Antarctic notothenioid fishes are highly stenothermal, yet their tolerance for warming is species-dependent. Because a body of literature points to the loss of cardiac function as underlying thermal limits in ectothermic animals, we investigated potential relationships among properties of ventricular mitochondrial membranes in notothenioids with known differences in both cardiac mitochondrial metabolism and organismal thermal tolerance. Fluidity of mitochondrial membranes was quantified by fluorescence depolarization for the white-blooded Chaenocephalus aceratus and the red-blooded Notothenia coriiceps. In these same membranes, lipid compositions and products of lipid peroxidation, the latter of which can disrupt membrane order, were analyzed in both species and in a second icefish, Pseudochaenichthys georgianus. Mitochondrial membranes from C. aceratus were significantly more fluid than those of the more thermotolerant species N. coriiceps (P < .0001). Consistent with this, ratios of total ... : Biederman et al (2019) 2009 vs 2015 comparisonPolar lipid composition of mitochondrial membranes prepared from cardiac ventricle of Chaenocephalus aceratus and Notothenia coriiceps. Measurements were performed in animals collected in the region of the Western Antarctic Peninsula during the austral fall seasons of 2009 and 2015.Biederman et al (2019) cardiolipinCardiolipin contents of mitochondrial membranes prepared from cardiac ventricle of Chaenocephalus aceratus, Notothenia coriiceps, and Pseudochaenichthys georgianus. Measurements were performed in animals collected in the region of the Western Antarctic Peninsula during the austral fall season of 2015.Biederman et al (2019) lipid peroxidationLipid peroxidation of mitochondrial membranes prepared from cardiac ventricle of Chaenocephalus aceratus, Notothenia coriiceps, and Pseudochaenichthys georgianus. Measurements were performed in animals collected in the region of the Western Antarctic Peninsula during the austral fall season of 2015.Biederman et al ...